30 years of Acta D. Issue 2 (10th February 2023) - Garman, Elspeth F.; Read, Randy J.; Bond, Charles S.
Abstract : Celebrating 30 years of Acta D and looking forward to the future of structural biology. Abstract : Celebrating 30 years of Acta D and looking forward to the future of structural biology.